Artificial Intelligence and Bullying (An Analysis of Luca's Animated Film) - Fanani, Moh Yusuf; Lailiyah, Siti; Lestari, Erawati Dwi (Proceeding International Conference on Education, 2023)
Artificial intelligence technology or artificial intelligence (AI) can be found in various aspects of life, for example in entertainment media such as animated films. One of the animated films that use AI technology is Luca. This film presents realistic visuals as it creates a vivid effect on the characters and the setting. Broadly speaking, the film Luca tells the story of the adventures of a sea monster boy named Luca Paguro and his relationship with humans. In this relationship, Luca and the sea monsters often experience bullying by humans. However, Luca is finally able to reconcile the relationship between his group and the humans who were initially lame. The purpose of this study is to describe the forms of bullying in Luca's film and criticize the society. In this film, three forms of bullying are found; verbal bullying, physical bullying, and relational bullying. Criticism in this film is directed at parents, perpetrators of bullying, and society that is exclusive and also bullies those who are considered different. Through the results of the analysis it can be concluded that Luca's film as one of AI's products can show a portrait of bullying as a social issue that is still commonly found in society. Through this film, the audience can monitor their surroundings as well as evaluate themselves so that bullying behavior can be reduced, or even completely eliminated.